Kinematic nonlinear controller for a miniature helicopter via Lyapunov techniques - Salinas, Lucio Rafael (2014)
This work proposes a kinematic nonlinear controller for an autonomous miniature helicopter that generates saturated reference velocity commands for accurate waypoint trajectory tracking. The control law design is based on a Lyapunov technique with a special choice of the system state equations using spherical coordinates. Stability of the control system is analyzed. Finally, simulation results are presented and discussed, which validate the proposed controller.